Keragaman Serangga pada Tanaman Terong Ungu (Solanum melongena) - Rizky Nadhif Nandana; Yayan Sanjaya; Topik Hidayat; Win Heri Sarfudin (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
Indonesia as a mega-biodiversity country has a very diverse diversity of insects. The diversity of these insects has both beneficial and detrimental roles. The beneficial role of insects is that they act as pollinators, predators of pests and regulators of wild plant populations, while the detrimental roles of insects are plant-eating pests and disease vectors in plants. Insects have many habitats, one of which is purple eggplant or solanum melongena. Eggplant is cultivated for consumption and contains many ingredients. This plant is widely cultivated because it contains nutrients consisting of minerals and vitamins such as A, B and C, is low in calories and fat, and contains some protein, fiber and carbohydrates. This research is included in the quantitative descriptive research. This research is located on the agricultural land of PT. BIO, which is located at Jl. Banjar Sari No. 38, Dusun Awisurat, Tanjungsari, Kec. Tanjungsari, Sumedang Regency, West Java and takes place for 2 weeks in November 2022. Insect data collection uses insect nets and data that can be analyzed using relative abundance and Shannon-Wiener diversity index values. The insects found consisted of 6 orders namely Diptera, Hemiptera, Coleoptera, Orthoptera, Mantodea and Hymenoptera. The six orders consist of 9 families. The eggplant planting area has a Shannon-Wiener diversity index value of 1.8 so that the planting area conditions are close to natural conditions with an index value of > 2. From the findings, insects can be classified into four groups based on their role in eggplant plants. Based on their roles, six pest species, three predator species, one pollinator species and one non-pest species. The abundance of insect species in eggplant planting fields has low criteria except for Henosepilachna vigintioctopunctata which is moderate. The level of insect diversity in purple eggplant plantings was moderate, with the species that had the highest abundance being Henosepilachna vigintioctopunctata